E-076 Percutaneous sclerotherapy for head and neck lymphatic malformations in neonates and infants (≤ 12 months): indications, technique, safety, and outcomes. (23rd July 2022) - Caton, M; Duvvuri, M; Baker, A; Smith, E; Narsinh, K; Amans, M; Hetts, S; Higashida, R; Cooke, D; Dowd, C
Abstract : Introduction/Purpose: Percutaneous sclerotherapy (PS) is an effective treatment for symptomatic lymphatic malformations (LM) of the head/neck. Some LMs present in the neonatal period with fulminant or rapidly progressing symptoms. The purpose of this study was to study the indications, technique, and efficacy of PS for head/neck LM in neonate and infant patients. Methods: We reviewed records of a large, single-institution vascular anomalies clinic. Patients who underwent PS for LM of the head/neck at age ≤ 12 months were studied. The clinical, anatomic, and technical aspects of each treatment, rates of procedural and laboratory complications, post-treatment clinical and imaging outcomes were analyzed. Results: 22 patients underwent 36 PS treatments during the first year of life. The median age at first PS was 6.2 months (range 2–320 days). Severe airway compromise was the most frequent indication (31.8%) followed by poor feeding, pain/discomfort, motor skill delay, rapid lesion growth (9.1%, each), and retinal hemorrhage (4.5%). 72.7% of LM were DeSerres Grade ≥ 3. Sclerosants included doxycycline (80.5% of cases), sodium tetradecyl (55.5%), bleomycin (11.1%) and ethanol (2.8%). There were no procedural complications; sclerosant-related complications included transient metabolic acidosis (8.3%) and hemolytic anemia (5.5%). Median clinical follow-up duration was 3.7 years, IQR 0.6–4.8 years). 47.6% of patients showed >75% lesion size reduction and 19.0% showed minimal response (<25% lesion reduction). At last follow-up, 71.4% of children were developmentally normal and asymptomatic, 23.8% had mild/intermittent ongoing symptoms, and 4.8% required tracheostomy and long-term care assistance. Conclusion: PS is a safe and effective treatment for carefully selected large or symptomatic LM of the head and neck in neonates and infants. Disclosures: M. Caton: None. M. Duvvuri: None. A. Baker: None. E. Smith: None. K. Narsinh: None. M. Amans: None. S. Hetts: None. R. Higashida: None. D. Cooke: None. C. Dowd: None.